Communication To Foster Technology Acceptance Of Telemedicine Among Medical Personnel Under The Covid-19 Epidemic: Case Studies In Medical School Hospitals In Thailand - Chankrachang, Pannapat; Oraphan, Peerayut (Journal of Business, Innovation and Sustainability (JBIS), 2025)
This research, titled "Communication to Foster Technology Acceptance of Telemedicine Among Medical Personnel Under the COVID-19 Epidemic: Case Studies in Medical School Hospitals in Thailand," aimed to (1) study the communication planning strategies for fostering acceptance of telemedicine systems among medical personnel, and (2) examine the factors influencing their acceptance of telemedicine technology. The study employed a qualitative methodology using in-depth interviews with purposively sampled participants, including communication planners and medical personnel, from Chulalongkorn Hospital and Siriraj Hospital. Data were analyzed through thematic content analysis, ensuring alignment with research objectives. Findings revealed that communication strategies in both hospitals shared four common objectives: (1) raising awareness about telemedicine systems, (2) reducing COVID-19 transmission risks, (3) optimizing hospital bed usage to accommodate critical cases, and (4) enhancing healthcare service capabilities. Factors influencing acceptance included seven key elements: (1) image, (2) subjective norms, (3) voluntariness, (4) job relevance, (5) perceived ease of use, (6) output quality, and (7) result demonstrability, with the supplementary variable of experience identified as the most significant. Personal experience enabled medical personnel to recognize telemedicine’s benefits and influenced other factors. Conversely, image had the least impact, as neither hospital prioritized it during system implementation. The results emphasize that the success of telemedicine adoption relies heavily on strategic communication planning tailored to organizational contexts and the experiences of medical personnel. These findings contribute to the development of effective communication frameworks to promote technology acceptance in healthcare.